Integrating SERVQUAL and Importance Performance Analysis to Prioritize Service Improvements in Modern Retail: A Case Study of XYZ Store - Sajidin, Mochammad Afif; Andesta, Deny; Nuruddin, Mochammad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Service quality is a critical determinant of competitiveness in modern retail, particularly as rapid growth in small convenience stores intensifies customer expectations. Specific Background: XYZ Store has experienced declining customer satisfaction, requiring a systematic evaluation of service delivery using established measurement frameworks. Knowledge Gap: Despite the extensive use of SERVQUAL and Importance Performance Analysis (IPA) in service research, limited studies integrate both methods to diagnose priority improvements in small-scale retail settings. Aims: This study aims to measure service quality at XYZ Store, identify performance gaps across SERVQUAL dimensions, and prioritize improvement strategies using IPA. Results: Analysis of 100 respondents showed all SERVQUAL attributes were valid and reliable, with an overall gap score of –0.74 and a service quality index (Q) of 0.84, indicating service performance below expectations. IPA mapping revealed four critical attributes—store layout (T3), complaint handling (RP3), facility conditions (T1), and product availability (RL2)—requiring immediate improvement. Novelty: This research offers an integrated SERVQUAL–IPA approach that produces a precise, actionable prioritization of service weaknesses in a small retail context. Implications: Findings provide managerial guidance for enhancing operational performance, increasing customer satisfaction, and strengthening competitive positioning in the retail sector. Highlights: Identifies critical service gaps with an integrated SERVQUAL–IPA approach. Highlights four priority attributes needing immediate improvement. Provides actionable strategies to enhance customer satisfaction and competitiveness. Keywords: SERVQUAL, IPA, Service Quality, Customer Satisfaction, Retail Management